Functionalized nickel oxide hole contact layers: work function versus conductivity - Hietzschold, Sebastian; Hillebrandt, Sabina; Bombsch, Jakob; Rohnacher, Valentina; Pucci, Annemarie; Beck, Sebastian; Lovrinčić, Robert (ACS applied materials & interfaces, 2017)
Nickel oxide (NiO) is a widely used material for efficient hole extraction in optoelectronic devices. However, its surface characteristics strongly depend on the processing history and exposure to adsorbates. To achieve controllability of the electronic and chemical properties of solution-processed nickel oxide (sNiO), we functionalize its surface with a self-assembled monolayer (SAM) of 4-cyanophenylphosphonic acid. A detailed analysis of infrared and photoelectron spectroscopy shows the chemisorption of the molecules with a nominal layer thickness of around one monolayer and gives an insight into the chemical composition of the SAM. Density functional theory calculations reveal the possible binding configurations. By the application of the SAM, we increase the sNiO work function by up to 0.8 eV. When incorporated in organic solar cells, the increase in work function and improved energy level alignment to the donor does not lead to a higher fill factor of these cells. Instead, we observe the formation of a transport barrier, which can be reduced by increasing the conductivity of the sNiO through doping with copper oxide. We conclude that the widespread assumption of maximizing the fill factor by only matching the work function of the oxide charge extraction layer with the energy levels in the active material is a too narrow approach. Successful implementation of interface modifiers is only possible with a sufficiently high charge carrier concentration in the oxide interlayer to support efficient charge transfer across the interface.
Publication date (web): October 20, 2017
Gesehen am 19.06.2018